2020
DOI: 10.15376/biores.15.3.5305-5315
|View full text |Cite
|
Sign up to set email alerts
|

Seawater degradation resistance of straw fiber-reinforced polyvinyl chloride composites

Abstract: To investigate the effect of seawater degradation on the mechanical, wear, and thermal properties of plant fiber-reinforced polymer composites, the seawater immersion test was performed on four types of straw fiber (wheat straw (WS), rice straw (RS), corn straw (CS), and sorghum straw (SS))-reinforced polyvinyl chloride (PVC) composites. The results revealed that seawater immersion would result in poor mechanical, wear, and thermal properties, and lower two-phase bonding quality, thermal mass loss, and thermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The thermoplastic polymer do not form crosslinks, melts completely when a specific temperature is applied and are recyclable, while the thermoset resins are low-molecular-weight molecules, which form crosslinks in the curing process, promoting chemical bonding between macromolecular chains and creating a three-dimensional network, the cure process is irreversible and thermoset cannot be recycled by thermal action [46][47][48] . Among the thermoplastic polymers used as matrix, polyethylene (PE) [49] , polypropylene (PP) [50] , polyvinyl chloride (PVC) [51] , and polystyrene (PS) [52] stand out. Among the thermoset polymers, polyurethane (PU) [53] , epoxies [54] , and polyesters [55] are commonly used.…”
Section: Polymer Matrixmentioning
confidence: 99%
“…The thermoplastic polymer do not form crosslinks, melts completely when a specific temperature is applied and are recyclable, while the thermoset resins are low-molecular-weight molecules, which form crosslinks in the curing process, promoting chemical bonding between macromolecular chains and creating a three-dimensional network, the cure process is irreversible and thermoset cannot be recycled by thermal action [46][47][48] . Among the thermoplastic polymers used as matrix, polyethylene (PE) [49] , polypropylene (PP) [50] , polyvinyl chloride (PVC) [51] , and polystyrene (PS) [52] stand out. Among the thermoset polymers, polyurethane (PU) [53] , epoxies [54] , and polyesters [55] are commonly used.…”
Section: Polymer Matrixmentioning
confidence: 99%
“…A reliability study was conducted on a wood–plastic composite hull, and the limit state equation of the composite-reinforced panel material was proposed [ 14 , 15 ]; the effects of the coupling agent, test frequency and stress ratio on the fatigue life and reliability of wood–plastic composite panels used in footbridges were investigated experimentally [ 16 ]. The surface properties and structural strength of colored wood–plastic composites were studied under the corrosive environment of seawater, and the relationship between the coloring pigments and the reliability of the wood–plastic composites was analyzed [ 17 , 18 , 19 ]. The fatigue analysis and reliability of polypropylene (PP)/wood flour (WF) composites were investigated, and it was suggested that the fatigue life obtained from the lower 95% confidence limit can be used as a material reliability index for the safe fatigue design of composites [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%